2020
DOI: 10.1503/jpn.180098
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of cocaine use disorder accounting for phenotypic heterogeneity and gene–environment interaction

Abstract: Background: Phenotypic heterogeneity and complicated gene-environment interplay in etiology are among the primary factors that hinder the identification of genetic variants associated with cocaine use disorder. Methods: To detect novel genetic variants associated with cocaine use disorder, we derived disease traits with reduced phenotypic heterogeneity using cluster analysis of a study sample (n = 9965). We then used these traits in genome-wide association tests, performed separately for 2070 African Americans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
(67 reference statements)
1
23
0
Order By: Relevance
“…Interestingly, this study estimated a SNP-based heritability (h 2 SNP ) for cocaine dependence around 0.27-0.30 using two different approaches, and very similar results were obtained using GWAS data from Gelernter et al (h 2 SNP = 0.28; Table 3) [46]. Two GWAS on CUD have been recently published, one accounting for gene-environment interactions [6], and another one evaluating time to develop dependence [47] (Table 3). In the first one, two GWS hits were found associated with DSM-5 diagnostic criterion counts in AA individuals (N = 2998) [6], only when the interactive effect of childhood environmental risk factors were considered: change in residence for rs10188036 in TRAK2 and household drinking and illicit drug use for del-13:61274071 in LINC00378 (Table 3).…”
Section: Genetic Architecture Of Cocaine Addictionsupporting
confidence: 65%
See 1 more Smart Citation
“…Interestingly, this study estimated a SNP-based heritability (h 2 SNP ) for cocaine dependence around 0.27-0.30 using two different approaches, and very similar results were obtained using GWAS data from Gelernter et al (h 2 SNP = 0.28; Table 3) [46]. Two GWAS on CUD have been recently published, one accounting for gene-environment interactions [6], and another one evaluating time to develop dependence [47] (Table 3). In the first one, two GWS hits were found associated with DSM-5 diagnostic criterion counts in AA individuals (N = 2998) [6], only when the interactive effect of childhood environmental risk factors were considered: change in residence for rs10188036 in TRAK2 and household drinking and illicit drug use for del-13:61274071 in LINC00378 (Table 3).…”
Section: Genetic Architecture Of Cocaine Addictionsupporting
confidence: 65%
“…In addition, a cluster analysis was performed to divide the sample in five CUD groups. For the subtypes 4 (N = 3258) and 5 (N = 1916; the highest heritable and heavy-cocaine-use clusters) they identified 11 additional GWS loci for which the effect on CUD was moderated by environmental factors (Table 3), highlighting the importance of considering environmental interactions in the statistical models [6]. In addition, this study supports the idea that CUD subjects can be decomposed into different subgroups, as previously mentioned, and the study of more homogeneous subgroups may result in more powerful genetic analyses [5].…”
Section: Genetic Architecture Of Cocaine Addictionmentioning
confidence: 99%
“…They also found positive genetic correlations with schizophrenia, ADHD, major depression, and risk-taking, in line with phenotypic correlations (despite the number of cases being less than recommended for LD score regression; Table 1 ). Another recent study used cluster analyses to identify CocUD subtypes with reduced phenotypic heterogeneity, one potential barrier to identifying significant genetic variants for psychiatric disorders (Sun, Kranzler, Gelernter, & Bi, 2020 ). Still, few genetic findings have replicated amongst GWAS of CocUD; we expect the number of robust, replicable findings to increase with larger sample sizes (similar to other SUDs).…”
Section: Genetics Of Sudsmentioning
confidence: 99%
“…SHR/NCrl self-administered more cocaine than SHR/NHsd under the FR1 schedule and also emitted more cocaine seeking responses and completed more cocaine seek-take cycles under the chained schedule. Heritability estimates indicated that 26% - 40% of the variances for our cocaine use traits can be explained by additive genetic factors, a key finding because cocaine use disorders in people are heritable on the order of 40% - 70% [78, 79]. As discussed in section 4.2, four of our premorbid cocaine vulnerability traits (impulsivity, compulsivity, reactivity to sucrose reward and initial sensitivity to acute 20 mg/kg cocaine) showed substrain differences, with 22% - 38% of their phenotypic variances explained by additive genetic factors.…”
Section: Discussionmentioning
confidence: 99%